2022
DOI: 10.3389/fphar.2022.1032282
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the action mechanism of paeoniflorin in suppressing pancreatic cancer: A network pharmacology study and experimental validation

Abstract: Background: Paeoniflorin (PF) is the main active component of Chinese herbaceous peony that has been shown to have an anti-tumor effect. However, there are few studies on the prevention and treatment of pancreatic cancer with PF.Methods: We gathered Microarray data pertaining to paeoniflorin intervention in pancreatic cancer by utilizing the GEO database (GSE97124). Then, the DEGs were filtered by the 33R program. RNA-seq data of pancreatic cancer and normal tissue samples were taken from the TCGA and GTEx dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…PF is the primary active compound of Paeonia suffruticosa , Paeonia suffruticosa , and Paeonia lactiflora and has good, anti-tumor, anti-ulcer, immunoregulatory, and neuroprotective effects ( 25 , 26 ). In a network pharmacology and experimental validation study, Cao et al ( 58 ) revealed that PF can regulate inflammatory factors including IL-6 and IL-10 expression through the p38 MAPK signaling pathway in the treatment of pancreatic cancer. Sun et al ( 59 ) found that PF downregulated IL-18, TNF-α, and IL-1β expression levels in a rat model of diabetic foot ulcers and was related to NLRP3/ASC/caspase-1 inflammasome formation and NF-κB transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PF is the primary active compound of Paeonia suffruticosa , Paeonia suffruticosa , and Paeonia lactiflora and has good, anti-tumor, anti-ulcer, immunoregulatory, and neuroprotective effects ( 25 , 26 ). In a network pharmacology and experimental validation study, Cao et al ( 58 ) revealed that PF can regulate inflammatory factors including IL-6 and IL-10 expression through the p38 MAPK signaling pathway in the treatment of pancreatic cancer. Sun et al ( 59 ) found that PF downregulated IL-18, TNF-α, and IL-1β expression levels in a rat model of diabetic foot ulcers and was related to NLRP3/ASC/caspase-1 inflammasome formation and NF-κB transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (59) found that PF downregulated IL-18, TNF-α, and IL-1β expression levels in a rat model of diabetic foot ulcers and was related to NLRP3/ASC/caspase-1 inflammasome formation and NF-κB transcription. Several studies have revealed that PF regulates the activation of immune cells, decreases the release of inflammatory cytokines, and participates in the regulation of the GPCR and PI3K/AKT/mTOR pathways (58)(59)(60)(61)(62)(63). PF has also been shown to regulate GPCR signaling by suppressing the expression of β-arrestin 2 and upregulating cAMP-PKA signaling, and this regulation was important for its therapeutic effect in rheumatoid arthritis (60).…”
Section: Discussionmentioning
confidence: 99%
“…This result found that HYWZF treatment increased the expression levels of ZO-1, occludin, and claudin-5 proteins, indicating that HYWZF affected tissue integrity and barrier function. HE staining revealed that the retinal tissues in the model group were significantly swollen and infiltrated with inflammatory cells, indicating the presence of a large number of free radicals appeared[ 32 ]. Flow cytometry analysis further proved that there were a large number of ROS in the model group.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have witnessed an increasing interest in traditional Chinese medicine for cancer treatment, especially in reducing recurrence and metastasis of cancer and improving the quality of life for cancer patients. Several studies have shown that the active ingredients in RPR have inhibitory effects on the growth of various types of tumor cells, including lung cancer(20), pancreatic cancer(21), breast cancer(22), gastric cancer, colorectal cancer, bladder cancer and liver cancer(23). While many studies have shown the e cacy of single compounds in RPR extracts against diverse tumor types, comprehensive research on all active ingredients remains limited.…”
mentioning
confidence: 99%